Report on the guide lines to the diagnosis of leaking of library building at IIUM - Eusuf, Muhammad Abu (2017)
The purpose of this manuscript is to provide assistance on detecting weather tightness defects in buildings to- • Assistance, usual good practice standards to be followed by those diagnosing weather tightness defects, and • Contribute to the well-organized and effective repair of buildings that are leaking.